Learning media of digital booklets for class VIII junior high school - Andini, Nur Aisyah; Saifuddin, Much Fuad (Universitas Negeri Jakarta, 2023)
The learning system that has changed to online causes teachers to be creative in delivering material through digital learning media. Thus, research on the development of booklets into digital learning media needs to be carried out to assist teachers in facilitating learning and assisting students in understanding the material. This study aims to determine the quality and appropriateness of the content and its presentation as a medium for learning science in class VIII SMP material on the structure and function of plant tissue. This research method is a Research and Development (R & D) study, adapted from Thiagarajan’s 4 D (Define, Design, Development, and Disseminate) model. The data taken is the result of product assessment with a data collection instrument in the form of a questionnaire analyzed using descriptive-quantitative data. The resulting assessment from four media experts, four material experts, and a teacher showed the digital booklet in the very good category, with an average of 78.13% (media), 88.28% (material), and 96.88% (teacher). Besides, students gave very good responses., indicated by the acquisition of an average assessment of 94.89%. The digital booklet could be used as an alternative learning media on the structure and function of plant tissue.